Patent Law in Islamic Economics Challenges and Opportunities - Marwal, Muhammad Ilyas; Amir, Syafiq; Farah, Rina (Sharia Oikonomia Law Journal, 2024)
One important way to protect intellectual property rights is to use patent law to encourage creativity and innovation. In Islamic economics, the application of patent law raises several issues. This is because there are fundamental differences between the principles of Shari'a and some elements of conventional patent law. Since Islamic economics emphasizes justice, public interest, and equitable distribution of wealth, patent law must reflect these values. This study aims to identify and analyze the challenges and opportunities in the implementation of patent law in Islamic economics. Specifically, this study aims to understand the concepts and principles of patent law from an Islamic economic perspective, identify the main problems faced in the implementation of patent law in Muslim countries, explore opportunities for developing a patent legal framework that is in accordance with sharia principles, and provide. This research was conducted using qualitative methods, using literature studies and document analysis. Data were obtained from various sources, such as scientific journals, books, laws, fatwas, and other documents. The results of the study indicate that patent law in Islamic economics must balance individual rights and societal benefits. Some of the main problems identified include lack of knowledge about the importance of patents, inconsistencies between some aspects of conventional patent law and sharia principles, and resistance to changes in current regulations. According to this study, patent law in Islamic economics faces many challenges and opportunities. By incorporating sharia principles into the patent legal system, innovation and technological progress that benefit society can be increased.